2005
DOI: 10.1530/eje.1.01868
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered adipocyte function in polycystic ovary syndrome

Abstract: Background: Adipocytokines are produced by adipose tissue and have been thought to be related to insulin resistance and other health consequences. We measured leptin, adiponectin, and resistin simultaneously in women with polycystic ovary syndrome (PCOS) and age-and weight-matched controls. Our hypothesis was that these simultaneous measurements would help determine whether adipocytokine secretion is abnormal in PCOS independent of body mass and whether these levels are related to insulin resistance as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
84
1
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 32 publications
13
84
1
11
Order By: Relevance
“…44 Evidence for the effects of adiponectin on the human ovary is also derived from the observation of reduced adiponectin levels in women diagnosed with PCOS, independent of obesity. [45][46][47] Causation is less clear, as obesity and PCOS both cause hyperandrogenemia, 1,46 and adipose tissue synthesis of adiponectin is reduced by androgens. 48 Nonetheless, genomic studies support the view that hypoadiponectinemia is a causative agent in PCOS.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%
“…44 Evidence for the effects of adiponectin on the human ovary is also derived from the observation of reduced adiponectin levels in women diagnosed with PCOS, independent of obesity. [45][46][47] Causation is less clear, as obesity and PCOS both cause hyperandrogenemia, 1,46 and adipose tissue synthesis of adiponectin is reduced by androgens. 48 Nonetheless, genomic studies support the view that hypoadiponectinemia is a causative agent in PCOS.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%
“…Various PCOS phenotypes presumably result from the interaction between multiple predisposing genomic variants, each exerting only minor effects and strong environmental influences (2). As PCOS is associated with obesity, insulin resistance and compensatory hyperinsulinemia (3), disturbed secretion of adipokines (4) and an elevated risk for diabetes mellitus type 2 (T2DM) (5) and cardiovascular diseases (CVD) (6), the peroxisome proliferator-activated receptor gamma (PPARG) represents a strong candidate gene predisposing to PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured human theca cells, 17a-hydroxylase activity is increased by resistin in the presence of forskolin or forskolinGinsulin, suggesting a role of resistin in stimulation of androgen production by theca cells (Munir et al 2005). Moreover, some studies have shown elevated concentrations of serum resistin in women with polycystic ovary syndrome (Panidis et al 2004, Carmina et al 2005, Munir et al 2005, Yilmaz et al 2009, which is known to be associated with hyperinsulinemia, hyperandrogenism, and insulin resistance (Gambineri et al 2002). In mammals, insulin as well as insulin-like growth factor 1 (IGF1) is well known to play a key role on the development of antral follicles, i.e.…”
Section: Introductionmentioning
confidence: 99%